Alcohol consumption: Overview of international trends - Monteiro, M.; Rehm, J.; Taylor, B.; Stockwell, Tim (Elsevier Inc., 2008)
Alcohol consumption is a significant risk factor for the burden of disease worldwide. Both the average per capita consumption and the patterns of consumption are important dimensions which need to be taken into account when estimating the impact of alcohol in a population. Based on WHO guidelines for monitoring alcohol consumption and related harm, this review provides an overview of global and regional trends in alcohol consumption and related problems, methodological issues surrounding estimates of consumption, patterns and harms related to alcohol and the WHO alcohol database. © 2008 Copyright © 2008 Elsevier Inc. All rights reserved.